2022
DOI: 10.5603/cj.a2022.0056
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of lactate dehydrogenase in COVID-19: A systematic review and meta-analysis

Abstract: Background: This meta-analysis outlines the role of elevated lactate dehydrogenase (LDH) levels in assessing the severity of coronavirus disease 2019 . Methods: The current study was designed as a systematic review and meta-analysis. Embase, Pub-Med, Web of Science, Scopus and Cochrane Central Register of Controlled Trials were searched to identify the usefulness of LDH as a marker of COVID-19 severity. All extracted data were analyzed using RevMan V.5.4 or STATA V.14 software. Results: A total of 264 records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 38 publications
3
42
0
2
Order By: Relevance
“…In addition, our data showed than when LDH was less than 367.5 U/L and P/F was more than 164.5, the PPV to predict a CT score less than 12.5 was 80%; instead, if LDH was > 367.5 U/L and P/F < 164.5 the PPV to predict a CT score > 12.5 was 83.3%. Some studies showed that LDH usually increase in COVID-19 patients and it’s increase could predict severity [24] , [25] . LDH is a cytoplasmatic enzymes highly expressed in the lung, liver, hearth, kidney and skeletal muscle, generally release in blood after cell death: thus, the lung damage, frequently founded in COVID-19 postmortem pathology [26] , could increase LDH blood levels [27] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our data showed than when LDH was less than 367.5 U/L and P/F was more than 164.5, the PPV to predict a CT score less than 12.5 was 80%; instead, if LDH was > 367.5 U/L and P/F < 164.5 the PPV to predict a CT score > 12.5 was 83.3%. Some studies showed that LDH usually increase in COVID-19 patients and it’s increase could predict severity [24] , [25] . LDH is a cytoplasmatic enzymes highly expressed in the lung, liver, hearth, kidney and skeletal muscle, generally release in blood after cell death: thus, the lung damage, frequently founded in COVID-19 postmortem pathology [26] , could increase LDH blood levels [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Greater clinical value could be found in using KL-6 at admission to predict the subsequent course of COVID-19. Twelve studies involved in our meta-analysis assessed the KL-6 level according to the disease severity [ 6 , 8 , 14 , 19 , 20 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Our analysis demonstrated that there was a significantly higher level of KL-6 in patients suffering from severe COVID-19 than mild-to-moderate.…”
Section: Discussionmentioning
confidence: 99%
“…However, combining several additional factors can increase their predictive value [ 5 ]. Additional prospective disease severity predictor candidates have been developed with other molecules, e.g., ferritin, lactate dehydrogenase, serum amyloid A or soluble interleukin-2-receptor (sIL2-R), but these have also proven mostly insufficient and not specific enough [ 6 , 7 , 8 , 9 ]. Finally, soluble urokinase-type plasminogen activator receptor (suPAR) is a promising predictor factor, but more data are needed to establish its potential clinical utility [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that some micronutrient supplements may also help the immune system of a COVID-19 patient to maintain integrity. Due to their immunomodulatory effects, essential micronutrient supplements [11,12,13,14,15], e.g., zinc, have recently received critical examination. Zinc is a micronutrient critical for the growth, development, and maintenance of immune barriers, such as the skin and mucous membranes.…”
Section: Introduction and Objectivementioning
confidence: 99%